2019
DOI: 10.1111/mec.15254
|View full text |Cite
|
Sign up to set email alerts
|

Massive introgression of major histocompatibility complex (MHC) genes in newt hybrid zones

Abstract: Variation in the vertebrate major histocompatibility complex (MHC) genes is crucial for fighting pathogen assault. Because new alleles confer a selective advantage, MHC should readily introgress between species, even under limited hybridization. Using replicated transects through two hybrid zones between strongly reproductively isolated European newts, Lissotriton montandoni and L. vulgaris, we demonstrated recent and ongoing MHC class I and II introgression in the Carpathian region. The extent of introgressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 49 publications
0
38
0
Order By: Relevance
“…It is thus possible that these genes do not currently introgress more easily, but it is also possible that introgression extended beyond the scale of our sampling, making its detection difficult with the use of cline analysis. Indeed, we found in the IN zone pervasive introgression of major histocompatibility complex (MHC) genes, a prime target of balancing selection, although cline parameters for MHC were not distinguishable from the genome‐wide Q cline (Dudek, Gaczorek, Zieliński, Babik, ). Overall, our data indicate that genes at the tails of the genome‐wide distribution of divergence between species only occasionally are found in the tails of the introgression—as predicted if processes other than introgression dominated the buildup of genomic differentiation between hybridizing species (Wolf & Ellegren, ).…”
Section: Discussionmentioning
confidence: 95%
“…It is thus possible that these genes do not currently introgress more easily, but it is also possible that introgression extended beyond the scale of our sampling, making its detection difficult with the use of cline analysis. Indeed, we found in the IN zone pervasive introgression of major histocompatibility complex (MHC) genes, a prime target of balancing selection, although cline parameters for MHC were not distinguishable from the genome‐wide Q cline (Dudek, Gaczorek, Zieliński, Babik, ). Overall, our data indicate that genes at the tails of the genome‐wide distribution of divergence between species only occasionally are found in the tails of the introgression—as predicted if processes other than introgression dominated the buildup of genomic differentiation between hybridizing species (Wolf & Ellegren, ).…”
Section: Discussionmentioning
confidence: 95%
“…In geographically structured models of host-pathogen coevolution (which do not consider MHC explicitly), polymorphism is maintained over longer periods than in unstructured models, probably due to asynchrony of coevolutionary interactions [52,53]. Introduction of MHC alleles from other species via adaptive introgression [4,55,92] could also lead to patterns consistent with TSP. Instead of being an indirect result of other dynamics, long-term coexistence of divergent allelic lineages could also be selected for directly, for example, due to their functional distinctness [33].…”
Section: Trends In Geneticsmentioning
confidence: 99%
“…This antigen presentation is a crucial step in the adaptive immune response as it allows self/non-self discrimination by T cells, ultimately facilitating the recognition of infecting pathogens. The feature that distinguishes classical MHC genes (MHC genes hereafter) from other genes in the MHC region is their extreme polymorphism, with dozens to hundreds of allelic variants segregating in natural populations [3][4][5]. The polymorphism is most pronounced in the peptide-binding domain (PBD; see Glossary), in particular at peptidebinding sites (PBSs), amino-acid residues interacting directly with antigens [6].…”
mentioning
confidence: 99%
“…Noticeably, MHC-DAB richness (as well as STR richness) increased with increasing LDH-based admixture, thus supporting introgression as a non-negligible source of adaptive diversity in wild populations (Hedrick, 2013). Because adaptive genes undergoing balancing selection (RAA) are predicted to permeate into the gene pool of sink populations more readily than neutral ones (Schierup et al, 2000), introgression, even if limited, should be more pronounced for MHC than neutral markers (Dudek et al, 2019).…”
Section: Effects Of Human-mediated Introgression On Mhc Diversity and Conservation Remarksmentioning
confidence: 97%
“…As an interesting consequence, the RAA may facilitate the introduction and spread of novel, initially rare alleles into populations via introgression. For instance, Dudek et al (2019) demonstrated that introgression coupled with balancing selection caused a massive allelic exchange and overall higher MHC variation in a newt hybrid zone.…”
Section: Introductionmentioning
confidence: 99%